Towards mechanobiologically optimized mandible reconstruction: CAD/CAM miniplates vs. reconstruction plates for fibula free flap fixation: A finite element study - Ruf, Philipp; Orassi, Vincenzo; Fischer, Heilwig; Steffen, Claudius; Duda, Georg N.; Heiland, Max; Kreutzer, Kilian; Checa, Sara; Rendenbach, Carsten (Frontiers in Bioengineering and Biotechnology, 2022)
Due to their advantages in applicability, patient-specific (CAD/CAM) reconstruction plates are increasingly used in fibula free flap mandible reconstruction. In addition, recently, CAD/CAM miniplates, with further advantages in postoperative management, have been introduced. However, biomechanical conditions induced by CAD/CAM systems remain partially unknown. This study aimed to evaluate the primary fixation stability of CAD/CAM fixators. For a patient-specific scenario, the biomechanical conditions induced in a one segmental fibula free flap stabilized using either a CAD/CAM reconstruction plate or CAD/CAM miniplates were determined using finite element analysis. The main output parameters were the strains between intersegmental bone surfaces and stresses in the fixation systems due to different biting scenarios. CAD/CAM miniplates resulted in higher mechanical strains in the mesial interosseous gap, whereas CAD/CAM reconstruction plate fixation resulted in higher strains in the distal interosseous gap. For all investigated fixation systems, stresses in the fixation systems were below the material yield stress and thus material failure would not be expected. While the use of CAD/CAM miniplates resulted in strain values considered adequate to promote bone healing in the mesial interosseous gap, in the distal interosseous gap CAD/CAM reconstruction plate fixation might result in more beneficial tissue straining. A mechanical failure of the fixation systems would not be expected.